ALAT PEMANGGANG DENGAN TUAS PEMBALIK - Rinaldy, Rian; Hasbaini, Hasbaini; Saputra, Devi Satria; Ihsan, Ihsan (SULIWA: Jurnal Multidisiplin Teknik, Sains, Pendidikan dan Teknologi, 2025)
The rapid development of science and technology has brought significant changes to people's lifestyles. In general, the roasting process begins with preparing food, arranging it, and roasting it using a grill made of wire mesh. To achieve optimal results, this device requires manual airflow to ensure even cooking. This method demands a worker to continuously blow on the fire, which is quite time-consuming. Based on this issue, the researcher has designed a grilling tool with a flip lever that operates by pulling the lever. The food clamp easily rotates, utilizing a blower to evenly distribute the embers for better cooking. The aim of the research was to be produced an innovative grilling product with a flip lever through experimental methods. The device operates by flipping the food after one side was cooked; pulling the flip lever allows the clamp to rotate easily. This process was repeated until the grilling was completed. After two grilling tested, the researcher found that the lever functions well and facilitates efficient flipping. The grill clamp securely holds the roasted food, keeping it stable while flipping, without the risk of slipping.